Psychological readiness for innovative activity and the ability to self-management of the police chiefs (Law and Safety, 2018)
It has been substantiated that modern realities dictate new requirements to the personality of a chief within law enforcement agencies, especially when his management activity is carried out in conditions that are characterized by their uncertainty, tension and responsibility. The effectiveness and success of the entire law enforcement system, as well as the quality of performing police professional tasks depend on the capabilities and personal qualities and competencies of a police chief. And the ability to act quickly in a changing environment and psychological readiness for innovative activity should provide a chief with the opportunity to improve the police work.Therefore, the objective of the article was empirical grounding of peculiarities of psychological readiness for innovative activity and the ability to self-management of the police chiefs with different level of readiness for innovative activity.The author of the research has used “Psychological Readiness for Innovation” (V. E. Klochko, O. M. Krasnoryadtseva) and “Ability to Self-Management” (N. M. Peisakhov) methods. The sample consisted of 316 heads of police departments.The author has theoretically grounded that psychological readiness for innovative activity and ability to self-management are considered as important personal traits of a police chief within professional activity. Empirical results have demonstrated that a group with an average level of readiness for innovative activity reveals the largest number of meaningful interactions, which include criteria for assessing quality, the ability to adjust their own goals while performing their professional tasks, and the tendency to increase the entire system of interpersonal relations. There were no relationships among law enforcement officers with a high degree of readiness, which led to the conclusion that such law enforcement officers with a higher level of readiness for innovative activity, are characterized by higher estimates of self-management indicators. It has been also established that law enforcement officers with a low level of readiness for innovative activity have an increase in the ability to correct the actual actions, characteristics of communication and behavioral patterns, as well as the system of self-management in general.It has been stressed that a well-developed indicator of self-management will help the police chief in planning new goals, finding new solutions in difficult situations.
Keywords: personality; law enforcement agencies; police chief; managerial activity; psychological readiness; innovative activity; self-management